Arbovirus studies of bats from Zulia state: serological survey for Venezuelan, eastern and western encephalitis virus antibodies, february 1976 - Dickerman, Robert; Ryder, Slavia; Martin, Mary (Investigación Clínica, 2013)
One hundred and forty five bats of 13 species collected during February 1916 at three sites in the State of Zulía, Venezuela, were negative for hemagglutination-inhibition (H 1) and neutralization antibodies to Venezuela n encephalitis virus. One hundred and thirty seven of these were also negative for H I antibodies to both Eastern and Western encephalitis viruses. Due to small series for most specíes in the sample, negative results are difficult to interpret.